2014
DOI: 10.1038/ncomms4238
|View full text |Cite
|
Sign up to set email alerts
|

Structural origins of Johari-Goldstein relaxation in a metallic glass

Abstract: Johari-Goldstein or b relaxation, persisting down to glassy state from a supercooled liquid, is a universal phenomenon of glassy dynamics. Nevertheless, the underlying micromechanisms leading to the relaxation are still in debate despite great efforts devoted to this problem for decades. Here we report experimental evidence on the structural origins of Johari-Goldstein relaxation in an ultra-quenched metallic glass. The measured activation energy of the relaxation (B26 times of the product of gas constant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 35 publications
10
82
2
2
Order By: Relevance
“…This result is surprisingly consistent with the X-ray experiments in metallic glasses 50,51 , showing that the b relaxation originates from highly localized bond switching. More importantly, the individual b processes are found insensitive to the overall properties of the system.…”
Section: Correlation Between Different Triggers and Pel Constructionsupporting
confidence: 90%
“…This result is surprisingly consistent with the X-ray experiments in metallic glasses 50,51 , showing that the b relaxation originates from highly localized bond switching. More importantly, the individual b processes are found insensitive to the overall properties of the system.…”
Section: Correlation Between Different Triggers and Pel Constructionsupporting
confidence: 90%
“…Moreover, the low-temperature aging observed here can not be explained in simple terms of free volume, but rather comprises distinct changes in the CSRO though local optimization of atomic pair interactions. These findings are consistent with the emergent idea that low-temperature aging and the slow β relaxation can be characterized by short-range atomic rearrangements in loosely packed or weakly bonded regions [63,64]. In this section, we will discuss some important chemical aspects associated with the observed low-temperature aging behavior in this particular metallic glass system.…”
Section: B Atomic-scale Structural Changes During β Relaxationsupporting
confidence: 80%
“…It is known that the flow phenomenon in MG is the percolation of the localized flow units 12,14,21 . To detect the extreme slow hidden flow before yielding or microscopic structural evolution during GLT, we applied Dynamical Mechanical Spectrum (DMS) measurement, which is a sensitive method to detect the viscoelastic properties of MGs [34][35][36] .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the stress-induced instantaneous flow of yield, recent experiments and numerical simulations also demonstrated that a glass subject to stress, which is much smaller than its normal yield strength, can also undergo an extreme slow flowing, which is hard to be detected within a short period of time due to the slowness [4][5][6][7] . On the other hand, the universal nano-scaled localized b-relaxation in metallic glassy state has been observed before the large-scale a-relaxation, which has been demonstrated to be related to the nano-scaled microscopic hidden flowing phenomenon [8][9][10][11][12] . However, the structural origin of the flowing phenomena in metallic glasses (MGs) such as the slow flowing and instantaneous flow of yield, elastic and plastic deformations, the transition between the b-relaxation to the a-relaxation and glass to supercooled liquid transition are not clear yet due to the lack of clear structural information.…”
mentioning
confidence: 99%